The Role of Religion and Spirituality in the Life of the Elderly in the Period of Coronavirus Disease 2019 (COVID-19) Pandemic: A Systematic Review - Farzin Bagheri Sheykhangafshe; Ali Fathi Ashtiani (مطالعات اسلام و روانشناسی, 2021)
The coronavirus disease 2019 (COVID-19) first spread from Wuhan City, Hubei Province, China, and in less than two months, it became a worldwide epidemic, according to the World Health Organization; thus, this review research was conducted with the aim of discovering the role of religion and spirituality in the life of the elderly in the period of coronavirus disease 2019 (COVID-19) pandemic. In this systematic review research, the keywords of "religion", "spirituality", "elder", "older adults", and "coronavirus 2019 (COVID-19)", appeared in the title and abstract of articles, were searched in databases of GoogleScholar, PubMed, Scopus, and ScienceDirect. All related English-language printed full-text articles, published in 2020 and 2021, were selected. The PRISMA checklist was used to review and control the quality of articles. The findings showed that the elderly who adhere to the religion and spirituality in the period of coronavirus disease 2019 pandemic had a better mental health. In addition, having religious beliefs causes people to create meaning and peace in their lives that it leads to the decrease of fear and anxiety resulted from coronavirus disease 2019 pandemic. Indeed, the elderly who have a high spiritual level have a better psychological resilience and flexibility that causes them to be aware of situations and to perceive the created pressure and pain more tolerably. Therefore, it can be understood that the religion and spirituality have many benefits for not only the elderly but all people of all ages that it is necessary to provide some education in textbooks (in the form of workshops) for improving spirituality.